Spremljanje na delovnem mestu kot učna izkušnja - Makovec, Danijela (Revija za elementarno izobraževanje, 2020)
Job shadowing as learning experience. We present job shadowing as an activity through which we can enable an individual to gain insight into what work an individual performs in a particular job, while at the same time taking the individual’s experience as a starting point from which learning can emerge. The first part of the text presents the theoretical starting points for work-based learning and job shadowing; in the second part, we present the results of the analysis of students’ reflections after the shadowing experience. The findings show that students found job shadowing extremely positive, as well as an experience that encouraged them to reflect on issues related to different aspects of the profession. In conclusion, we discuss whether job shadowing is an activity appropriate for use in studies for teaching professions.